Formulation of Temulawak for Improvement of the Organoleptic Characteristics (TROPICAL WETLAND JOURNAL, 2019)
Indonesia is a country rich in diversity of herbs and spices. As many as 20,000 plant species on earth can be used as a medicine and 11 percent or as much as more than 2,200 kinds of medicinal plants there are hiking Indonesia. One of the medicinal plants that have the potential to increase in value-added is Temulawak. In the area of Borneo total Temulawak in 2014 is 162.212 productions. One of the medicinal plants that have the potential to increase in value-added is Temulawak (Curcuma xanthorrhiza Roxb). Temulawak is one of the herbs that have the taste, aroma, and color typical of Rhizome Curcuma. Processing of Curcuma crops in Indonesia many carried out the purpose of this research is to know the influence of the number of concentration dilution Curcuma, and type of sugar (aren and sand), against the chemical properties and the acceptance of consumers, drink temulawak to enhance the consumer's receipt against the taste, the aroma of variant Temulawak. Manufacture of Temulawak has done with added sugar, Palm sugar, pandan leaves, and tamarind, with different concentrations, then analyzed the nutritional components, power thank consumers and consumer purchase interest. The results showed that the variation in the concentration of sugar concentration and Temulawak to sugar levels, variations in the concentration of sugar concentration and Temulawak to pH levels, and concentration of sugar concentration and Temulawak effect on total dissolved solids. Overall organoleptic results obtained 5% concentration of the sample extract and sugar concentration Temulawak 6% most preferred panelists.